Coffee and tea consumption and risk of prostate cancer in the European Prospective Investigation into Cancer and Nutrition - Sen,A; Papadimitriou,N; Lagiou,P; Perez-Cornago,A; Travis,RC; Key,TJ; Murphy,N; Gunter,M; Freisling,H; Tzoulaki,I; Muller,DC; Cross,AJ; et al. (International Journal of Cancer, 2019)
The epidemiological evidence regarding the association of coffee and tea consumption with prostate cancer risk is inconclusive, and few cohort studies have assessed these associations by disease stage and grade. We examined the associations of coffee (total, caffeinated and decaffeinated) and tea intake with prostate cancer risk in the European Prospective Investigation into Cancer and Nutrition. Among 142,196 men, 7,036 incident prostate cancer cases were diagnosed over 14 years of follow-up. Data on coffee and tea consumption were collected through validated country-specific food questionnaires at baseline. We used Cox proportional hazards regression models to compute hazard ratios (HRs) and 95% confidence intervals (CI). Models were stratified by center and age, and adjusted for anthropometric, lifestyle and dietary factors. Median coffee and tea intake were 375 mL/day and 106 mL/day, respectively, but large variations existed by country. Comparing the highest (median of 855 mL/day) versus lowest (median of 103 mL/day) consumers of coffee and tea (450 mL/day versus 12 mL/day) the HRs were 1.02 (95% CI, 0.94-1.09) and 0.98 (95% CI, 0.90-1.07) for risk of total prostate cancer, and 0.97 (95% CI, 0.79-1.21) and 0.89 (95% CI, 0.70-1.13) for risk of fatal disease, respectively. No evidence of association was seen for consumption of total, caffeinated or decaffeinated coffee or tea and risk of total prostate cancer or cancer by stage, grade or fatality in this large cohort. Further investigations are needed to clarify whether an association exists by different preparations or by concentrations and constituents of these beverages. This article is protected by copyright. All rights reserved.